1990
DOI: 10.1002/ijc.2910450534
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of HTLV‐I to rabbits via semen and breast milk from seropositive healthy persons

Abstract: Four rabbits inoculated intravenously with milk cells from 4 post-partum women seropositive for human T-cell leukemia virus type I (HTLV-I) and one rabbit inoculated with semen cells from a seropositive healthy man seroconverted for HTLV-I after 3-5 weeks but no seroconversion occurred in 2 rabbits inoculated with milk cells from a seronegative mother or with heated (56 degrees C, 30 min) milk cells from a seropositive mother. Attempts were made to isolate HTLV-I from peripheral blood lymphocytes harvested 5-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Transmission of HTLV-1 within families has been documented in different epidemiological studies carried out in several endemic areas around the world (41)(42)(43). However, the study reported here is the first in Colombia to follow up HTLV-1 infection dynamics in family clusters using immunological, virological and molecular markers.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of HTLV-1 within families has been documented in different epidemiological studies carried out in several endemic areas around the world (41)(42)(43). However, the study reported here is the first in Colombia to follow up HTLV-1 infection dynamics in family clusters using immunological, virological and molecular markers.…”
Section: Discussionmentioning
confidence: 99%
“…Inoculation of rabbits with cell-free concentrated HTLV-I virions 1ed to only a transient seroconversion, without detectable virus remaining after a few months (Miyoshi, 1994). Experimental transmission of HTL V -1 by b100d transfusion and from mother to offspring has also been observed in rabbits (Uemura et aL., 1986;Iwahara et al, 1990); as little as 0.01 mL of infected blood (corresponding to 1.7 x 104 lymphocytes) was capable of transmitting the virus. Hori et al (1995) have demonstrated intrauterine transmission of HTL V -1 in rats, a1beit at a 10w rate.…”
Section: Animal Model'ì Of Htl V-i Transmissionmentioning
confidence: 90%
“…HTL V -1 infection of rabbits or marmosets has been effected by intravenous or oral inoculation of HTL V -I-transformed and virus-producing cells (Kinoshita et al, 1985a;Yamanouchi et al, 1985;Uemura et al, 1986;Iwahara et al, 1990). Inoculation of rabbits with cell-free concentrated HTLV-I virions 1ed to only a transient seroconversion, without detectable virus remaining after a few months (Miyoshi, 1994).…”
Section: Animal Model'ì Of Htl V-i Transmissionmentioning
confidence: 99%
See 2 more Smart Citations